Nanoparticle behaviours in different biological media - Chua, Shu Fen (2016)
Formation of protein corona on the surface of nanoparticles has plenty of implications that would affect its cellular responses and thus changing its type of application. Inorganic nanoparticles hold great promise in food, cosmetic and biomedical applications. Studying the formation of corona on different widely used inorganic nanoparticles such as Titanium Dioxide (TiO2) and Zinc Oxide (ZnO) in different media would help to understand cell-nanoparticle interactions, cellular uptake and nanotoxicology. The presence of corona layer was qualified and quantified in this study. The presence of corona was identified using Fourier Transform Infrared Spectroscopy (FTIR) and Matrix Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry (MALDI-TOF). The amount of protein corona was quantified with micro BCA assay kit and Thermogravimetric Analysis (TGA). The formation of corona was found to be attributed to the presence of serum proteins that adhere to the surface of the nanoparticles. TiO2 which is positively charged in water was found to have more corona with higher serum content in medium. In contrast, negatively charged ZnO has higher protein content in RPMI medium containing 10% FBS than pure FBS. No protein corona was formed in media with high ionic strengths, PBS and RPMI.